Should we ban AirBnB? Short-term rental regulation and housing prices - Gonçalves, Duarte Maria Vilaça Delgado Vieira (2020)
In this paper, we analyze the impact of short-term rental on housing prices through a quasi-natural experiment that exploits a ban imposed in 2018 by the municipality of Lisbon in several of its neighborhoods. We rely on administrative data on the registries of short-term rental housing units and neighborhood housing prices and sold quantities in Lisbon and Porto to employ i) di erence-in di erences models and ii) event-study designs. Our ndings document a sizeable peak in new registries during the period between the announcement of the ban and its implementation, suggesting that agents were able to avoid the restriction. We also show that the ban fell short on its claims and validate the theory that buyers in the housing market value the option to participate in the short-term rental market upon purchase.